2019
DOI: 10.1128/jvi.01398-19
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Roles of the N-Terminal Region of HIV-1 SF2 Nef Are Mediated by Three Independent Protein Interaction Sites

Abstract: HIV-1 Nef promotes virus spread and disease progression by altering host cell transport and signaling processes through interaction with multiple host cell proteins. The N-terminal region in HIV-1 Nef encompassing residues 12 to 39 has been implicated in many Nef activities, including disruption of CD4 T lymphocyte polarization and homing to lymph nodes, antagonism of SERINC5 restriction to virion infectivity, downregulation of cell surface CD4 and major histocompatibility complex class I (MHC-I), release of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 85 publications
(159 reference statements)
1
18
0
Order By: Relevance
“…Our finding that Nef-mediated antagonism of SERINC3 displayed a distinct functional hierarchy among viral subtypes compared to that of SERINC5 indicates that these two closely related Nef activities are in fact functionally separable and further suggests that in vivo selection pressures to maintain these two Nef activities might differ. Indeed, the majority of subtype B Nef clones internalized SERINC5 efficiently but were impaired in their ability to counteract SERINC3, whereas SERINC3 antagonism activity was maintained in most Nef clones derived from subtypes A, C and D. We also discovered that these differences in SERINC3 antagonism could largely be attributed to residues in Nef's N-terminal anchor region, which allows the protein to interact with the inner leaflet of the plasma membrane as well as a variety of cellular kinases that are critical to its function [ 45 ]. In particular, we demonstrated that polymorphisms at residues 8 and 11 reduced Nef’s ability to co-localize with SERINC3 (but not SERINC5) based on PLA staining.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that Nef-mediated antagonism of SERINC3 displayed a distinct functional hierarchy among viral subtypes compared to that of SERINC5 indicates that these two closely related Nef activities are in fact functionally separable and further suggests that in vivo selection pressures to maintain these two Nef activities might differ. Indeed, the majority of subtype B Nef clones internalized SERINC5 efficiently but were impaired in their ability to counteract SERINC3, whereas SERINC3 antagonism activity was maintained in most Nef clones derived from subtypes A, C and D. We also discovered that these differences in SERINC3 antagonism could largely be attributed to residues in Nef's N-terminal anchor region, which allows the protein to interact with the inner leaflet of the plasma membrane as well as a variety of cellular kinases that are critical to its function [ 45 ]. In particular, we demonstrated that polymorphisms at residues 8 and 11 reduced Nef’s ability to co-localize with SERINC3 (but not SERINC5) based on PLA staining.…”
Section: Discussionmentioning
confidence: 99%
“…To gain insight into the molecular mechanism by which NEF impairs CD4 T‐cell help, we analyzed the activity of a series of mutant NEF proteins in the adoptive transfer model (Fig 3A). This included NEF F195A which lacks the ability to associate with the cellular p21‐activated kinase 2 (PAK2) to negatively modulate host cell actin dynamics and motility (O'Neill et al , 2006; Stolp et al , 2009; Stolp et al , 2012), a NEF variant with disrupted di‐leucine motif (NEF LLAA) that lacks the ability to internalize cell surface receptors such as CD4 (Craig et al , 1998; Greenberg et al , 1998), NEF AxxA in which an SH3 domain‐binding PxxP motif is disrupted and fails, e.g., to relocalize the TCR proximal kinase Lck from the plasma membrane to intracellular compartments (Saksela et al , 1995; Pan et al , 2012), as well as NEF variants carrying a deletion of an N‐terminal protein interaction platform (NEF ∆12‐39) or a mutation in an interaction motif within residues 12‐39 (NEF A32‐39) required for CD4 downregulation and SERINC5 antagonism (Ananth et al , 2019). Among these NEF mutants, only deletion/mutation of the motifs in the NEF N‐terminus impaired the ability of the viral protein to disrupt HEL‐specific antibody production (Fig 3B, Appendix Fig S1A).…”
Section: Resultsmentioning
confidence: 99%
“…The coding sequences for NEF SF2 A32‐39, NEF SF2 LLAA, or patient‐derived nef genes C122 and CB76 were cloned into pSTITCH using the restriction sites AgeI and PacI in a multiple‐cloning site that was previously subcloned along with IRES∆NGFR from pQCXIX backbone. The proviral constructs used are based on HIV‐1 NL4‐3 and either lack NEF expression (HIV‐1 ∆NEF), or encode for wild‐type NEF from HIV‐1 SF2 (HIV‐1 WT) or specific NEF mutants (Fackler et al , 2006; Ananth et al , 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations